Regional Dynamics, Urbanisms and Environment in Colombia. An approach for the Bogotá Region (2013)
This study evaluates and analyses the regional dynamics, urbanisms and environment in Colombia through studying the Bogotá region to determine the factors that affect the development and conformation of this region showing different trends with respect to other regions localized in developed countries. This analysis is conducted through the use of different methodologies applied in a longitudinal study of Bogotá to characterize patterns of the agglomeration process and concentration trends in this region while taking into account urbanism and environment. The results indicate that in the Bogotá region, the trend of conformation is varied, suggesting that this region has singular patterns of development and consolidation that depend on different features. Geographic possibilities, connectivity, availability of environmental resources and urban services are key factors in the Bogotá region, which have caused higher urbanization, characterized particularly by housing and limited productive chains. All findings of this study are important in the formulation of public policies according to regional dynamics and features found in the Bogotá region.